Quid de rebus Norvegiae in Nuntiis Finnorum Latinis (1989–2014) relatum sit - Pitkäranta, Reijo (Nordlit, 2014)
News pertaining to Norway reported in the Finnish Nuntii Latini, 1989–2014. The Nuntii Latini is a five-minute long, weekly news bulletin which the Finnish Broadcasting Company (Yle) has been broadcasting under the editorship of Tuomo Pekkanen and Reijo Pitkäranta for the last 25 years, ever since 1989 (http://yle.fi/nuntii). The texts covering the first ten-year period (1989–1999) were published in a book series of five volumes. In the preface to vol. IV one finds the opinions of various foreign colleagues concerning these news bulletins. One of these is Synnøve des Bouvrie, who praises them as “highly useful for learning living Latin”. Norwegian subject matters have been treated almost 70 times in these emissions, that is two or three times per year. National celebrations commemorating Norway’s independence, such as the hundredth anniversary of the dissolution of the union with Sweden (2005) and the two hundredth anniversary of the Constitution (2014), have been reported. Various news about the royal family has figured as well; so have parlamentary decisions and strains in the relations between Norway and other far-northern territories. Much space has been allotted to the Norwegian Nobel Committee and its laureates, not least in the year 2008, when Martti Ahtisaari of Finland received the Nobel Peace Price. We have also reported how the Norwegians have succeeded in various international surveys, such as how the countries of the world fared in terms of the equality of men and women, economic prosperity, public health, and general welfare. Nor have we avoided to give publicity to the many glorious victories that Norwegian athletes (such as Dæhli and Thorkildsen) have made in various competitions. Likewise, Magnus Carlsen’s great achievement when becoming the world’s Number 1 in chess has been praised. It would have been impossible if sad disasters that have befallen Norway were not carefully treated as well. More than anything the hideous crime that Anders Behring Breivik committed in the summer of 2011 belong in this category. However, even devastating storms, natural disasters, and conflagrations which took their toll on the population and nature, have figured in our Nuntii Latini.
Keywords: Nuntii Latini; Norvegia; rex Haraldus; Dæhlie; Thorkildsen; Carlsen; Breivik